Conversion journeys - Dufford, Sulaiman (Yayasan Ismail, 2004)
"Conversion Journeys" occur in inner space, the last frontier. So many are crossing over to a religion other than what they were born into, it is high time that notice is taken of these pioneers of inner space travel, and of their pilot for the journey, man among men, prophet among prophets, our beloved Prophet Muhammad, the peace and blessings of Allah be upon him. The simple, sincere stories in this book tell more of reversion than conversion, reversion to the original faith of the Prophet Adam, father of us all. But this book aims at more than pious devotion. This book brings to our attention not only the impressive sprectrum of conversion journeys, but also new ways of analyzing the dynamics of religious change sweeping the world today.